Cobalt-containing high-speed tool steel and preparation method thereof

By accurately controlling the alloy element content in Gaogong Steel, applying rare earth elements, and combining ultrasonic immersion and induction heating treatment, the problem of difficult balance between wear resistance and impact resistance of high engineering steel is solved, and the corrosion resistance and cold and heat resistance of the product are significantly improved.

CN119663093AActive Publication Date: 2025-03-21DALIAN YONGBAO NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202510181886.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-19
Publication Date
2025-03-21
Estimated Expiration
2045-02-19

AI Technical Summary

Technical Problem

When the existing high-tech steel improves wear resistance, it is easy to affect impact resistance, and the wear resistance, impact resistance and hardness are difficult to balance and coordinate, and the product has poor corrosion resistance and cold resistance.

Method used

The preparation method of cobalt-containing high-tech steel is adopted, and the performance of the steel ingot billet is optimized by precise control of the content of alloy elements such as C, Mo, W, V and Co, combined with the application of rare earth elements. The performance of the steel ingot billet is optimized by hydroxyapatite-based immersion adjustment and induction heating treatment based on hydroxyapatite modification and ultrasonic immersion adjustment and induction heating treatment of the modified solution.

Benefits of technology

The balance and coordination of wear resistance, impact resistance and hardness of high-tech steel has been achieved, and the corrosion resistance and cold resistance of products have been significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of high-speed tool steel, in particular to cobalt-containing high-speed tool steel and a preparation method thereof.The preparation method comprises the following steps that raw materials including, by weight, 55-60 parts of Fe, 2-5 parts of Mo, 2-4 parts of W, 0.5-0.8 part of V, 0.2-0.5 part of Co, 0.1-0.2 part of C and 0.1-0.2 part of rare earth elements are weighed; according to the cobalt-containing high-speed tool steel, through precise control over the content of alloy elements such as C, Mo, W, V and Co, ideal technical indexes of metallographic structures and machining performance are achieved, so that it is guaranteed that after heat treatment, ideal wear resistance and hardness are achieved, the wear resistance, impact resistance and hardness of a product are improved in a balanced and coordinated mode, and the effects of corrosion resistance and cold and heat resistance stability of the product are remarkable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-grade steel, and in particular to a cobalt-containing high-grade steel and a preparation method thereof. Background Art

[0002] High-speed steel is a complex steel type with a carbon content generally between 0.70% and 1.65%. It is also called high-speed steel and high-speed steel. It is mainly used as a high-carbon high-alloy ledeburite steel for high-speed cutting tools of machine tools. In order to improve the wear resistance of the existing high-speed steel, it is easy to affect the impact resistance of the product. At the same time, it is difficult to balance and coordinate the improvement of the wear resistance, impact resistance and hardness of the product. In addition, the corrosion resistance and cold and heat stability of the product are poor, which limits the use efficiency of the product. Summary of the invention

[0003] In view of the defects of the prior art, the purpose of the present invention is to provide a cobalt-containing high-tech steel and a preparation method thereof to solve the problems raised in the above background technology.

[0004] The present invention solves the technical problem by adopting the following technical solution: The present invention provides a method for preparing cobalt-containing high-tech steel, comprising the following steps: Step 1: weigh the raw materials according to weight: Fe 55-60 parts, Mo 2-5 parts, W 2-4 parts, V 0.5-0.8 parts, Co 0.2-0.5 parts, C 0.1-0.2 parts, rare earth elements 0.1-0.2 parts; Step 2: Smelt the Fe, Mo, W, V, Co and C in step 1 to form a melt, then add the rare earth element and continue smelting for 1-2 hours to obtain a casting liquid; Step 3, injecting the casting liquid into a metal mold preheated to 200-250° C. for casting to obtain a steel ingot; Step 4, immersing the steel ingot into a sufficient amount of a hydroxyapatite-modified immersion agent for ultrasonic immersion treatment, the ultrasonic immersion power is 350-400W, the ultrasonic time is 20min, and after the immersion is completed, the immersion is filtered and dried to obtain the immersion-treated steel ingot; Step 5, performing a solution treatment on the leached steel ingot, and then performing an aging treatment; Step six, coating the surface of the steel ingot processed in step five with the modifying liquid until the surface of the steel ingot is soaked, and then induction heating treatment is performed to obtain cobalt-containing high-tech steel.

[0005] Preferably, the rare earth element is a mixture of neodymium, gadolinium and scandium in a weight ratio of 2:1:1; The temperature of the solution treatment is 500-540°C for 1-2 hours; the temperature of the aging treatment is 350-380°C for 10-20 hours; Induction heating treatment adopts distributed induction heating treatment. The specific induction heating method is: First, induction heating was performed at 790-800°C for 2 h, then the temperature was lowered to 550-560°C at a rate of 1-3°C / min, induction heating was performed for 1 h, and finally air-cooled to room temperature.

[0006] Preferably, the preparation method of the hydroxyapatite-modified infusion agent is: S01: First, stir the hydroxyapatite in a sufficient amount of 5% potassium permanganate solution, then wash, filter and dry. Preheat the dried hydroxyapatite to 60°C and keep it warm. S02: 3-5 parts of hydroxyapatite treated with S01, 1-2 parts of stearic acid, 0.02-0.03 parts of manganese powder, 0.02-0.03 parts of chromium powder and 5-8 parts of sodium alginate solution are fully mixed, and then filtered and dried to obtain a hydroxyapatite-based conditioning agent; S03: heat-treating kaolin at 150-160° C. for 10-20 min, then air-cooling to room temperature, and fully blending 3-5 parts of heat-treated kaolin, 1-3 parts of aluminum borate whiskers, 5-8 parts of chitosan solution, and 2-3 parts of sodium dodecylbenzene sulfonate to obtain a kaolin composite whisker solution; S04: ultrasonically treat a hydroxyapatite-based conditioning agent and a kaolin compound whisker solution at a weight ratio of 2:5 to obtain a hydroxyapatite-modified conditioning agent.

[0007] The hydroxyapatite-modified leaching agent adopts hydroxyapatite to be activated by potassium permanganate solution, and then preheated, and mixed with stearic acid, manganese powder, chromium powder and sodium alginate solution to fully obtain the hydroxyapatite-based conditioning agent. Through the coordination between the raw materials and the coordination of kaolin compound whisker liquid, the performance effect of the product is improved by solid solution treatment and aging treatment during ultrasonic leaching. The kaolin compound whisker liquid is made of lamellar kaolin after thermal modification, and then through aluminum borate whiskers and Chitosan solution and sodium dodecylbenzene sulfonate are harmonized and coordinated, and the whisker structure of aluminum borate whiskers is used to harmonize sodium dodecylbenzene sulfonate, chitosan solution and kaolin. The kaolin composite whisker solution obtained is further synergistically improved. The hydroxyapatite-based regulator is obtained by harmonizing and coordinating raw materials such as manganese powder and chromium powder to obtain a hydroxyapatite-modified infusion regulator. After the ingot body is infused with the regulator, it is subjected to heat improvement treatment, and the grain refinement and strengthening effects are enhanced, and the performance coordination and performance stability of the product are further improved.

[0008] Preferably, the mass fraction of the sodium alginate solution is 2-5%; the mass fraction of the chitosan solution is 3-5%.

[0009] Preferably, the ultrasonic power of the ultrasonic treatment is 450-500W, and the ultrasonic time is 20-30min.

[0010] Preferably, the preparation method of the modified liquid is: S101: irradiating the wollastonite in a proton irradiation box for 10 to 15 minutes at an irradiation power of 350 to 400 W, and obtaining an irradiated wollastonite agent after the irradiation is completed; The irradiated wollastonite agent, lanthanum chloride solution and silane coupling agent KH550 are uniformly mixed in a weight ratio of (3-4):5:1 to obtain a wollastonite active solution; S102: adding yttrium oxide to the regulator in a weight ratio of 2:5, stirring and regulating, and after stirring, filtering and drying to obtain a regulated yttrium oxide body; The adjusted yttrium oxide body and wollastonite active liquid are mixed in a weight ratio of 3:5 and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 hours to obtain a modified liquid.

[0011] Preferably, the stirring temperature of the stirring and adjusting treatment is 55-60° C., the stirring speed is 350-400 r / min, and the stirring time is 1 hour; and the mass fraction of the lanthanum chloride solution is 2-5%.

[0012] Preferably, the regulator comprises the following raw materials in parts by weight: 2 to 3 parts of nano titanium dioxide, 3 to 5 parts of 5% dopamine hydrochloride solution by mass, 1 to 1.5 parts of urea, 2 to 4 parts of flaky boron nitride and 4 to 6 parts of 4% sodium lignin sulfonate solution by mass.

[0013] The modified liquid uses wollastonite to be irradiated with protons to optimize its activity performance, and then it is coordinated and matched with lanthanum chloride solution and silane coupling agent KH550. The raw materials are coordinated and matched with each other, and the coordinated matching of the adjusted yttrium oxide body is enhanced. The adjusted yttrium oxide body uses nano-titanium dioxide, 5% by mass dopamine hydrochloride solution, urea, flaky boron nitride and 4% by mass sodium lignin sulfonate solution to coordinate with each other. Nano-titanium dioxide and flaky boron nitride are used as matrix materials to improve the wollastonite. The system performance is strengthened by the needle-like structure of wollastonite. At the same time, the adjusted yttrium oxide body is blended and improved, and then it is coordinated and improved through induction heating treatment, so that the performance of the obtained product is further improved.

[0014] Preferably, the flake boron nitride has a layer thickness of 2 to 3 nm and a flake diameter of 1 to 3 µm.

[0015] The invention also provides a method for preparing cobalt-containing high-tech steel and the cobalt-containing high-tech steel prepared by the method.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The cobalt-containing high-tech steel of the present invention achieves ideal metallographic structure and processing performance technical indicators through precise control of the contents of alloying elements such as C, Mo, W, V and Co, thereby ensuring that the ideal wear resistance and hardness are achieved after heat treatment, optimizing the wear resistance, impact resistance and hardness balance and coordination improvement of the product, and the corrosion resistance and cold and heat stability of the product are significantly improved; the application of rare earth elements in high-tech steel has a significant effect, can refine the grains, improve the wear resistance, hardness and mechanical properties of high-tech steel, and can significantly improve the corrosion resistance and cold and heat stability of the material, the high-tech steel is immersed in a sufficient amount of hydroxyapatite-modified immersion agent for ultrasonic immersion treatment, and then the surface of the ingot is coated with a modified liquid to infiltrate the surface of the ingot, and through the coordination and synergy between the process raw materials, the wear resistance, impact resistance and hardness of the obtained product are balanced and coordinated, and the corrosion resistance and cold and heat stability of the product are significantly improved. DETAILED DESCRIPTION

[0017] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] A method for preparing a cobalt-containing high-tech steel in this embodiment comprises the following steps: Step 1: weigh the raw materials according to weight: Fe 55-60 parts, Mo 2-5 parts, W 2-4 parts, V 0.5-0.8 parts, Co 0.2-0.5 parts, C 0.1-0.2 parts, rare earth elements 0.1-0.2 parts; Step 2: Smelt the Fe, Mo, W, V, Co and C in step 1 to form a melt, then add the rare earth element and continue smelting for 1-2 hours to obtain a casting liquid; Step 3, injecting the casting liquid into a metal mold preheated to 200-250° C. for casting to obtain a steel ingot; Step 4, immersing the steel ingot into a sufficient amount of a hydroxyapatite-modified immersion agent for ultrasonic immersion treatment, the ultrasonic immersion power is 350-400W, the ultrasonic time is 20min, and after the immersion is completed, the immersion is filtered and dried to obtain the immersion-treated steel ingot; Step 5, performing a solution treatment on the leached steel ingot, and then performing an aging treatment; Step six, coating the surface of the steel ingot processed in step five with the modifying liquid until the surface of the steel ingot is wetted, and then induction heating treatment is performed to obtain the cobalt-containing high-tech steel of the present invention.

[0019] The rare earth elements in this embodiment are neodymium, gadolinium, and scandium mixed in a weight ratio of 2:1:1; The temperature of the solution treatment is 500-540°C for 1-2 hours; the temperature of the aging treatment is 350-380°C for 10-20 hours; Induction heating treatment adopts distributed induction heating treatment. The specific induction heating method is: First, induction heating was performed at 790-800°C for 2 h, then the temperature was lowered to 550-560°C at a rate of 1-3°C / min, induction heating was performed for 1 h, and finally air-cooled to room temperature.

[0020] The preparation method of the hydroxyapatite-modified infusion agent of this embodiment is as follows: S01: First, stir the hydroxyapatite in a sufficient amount of 5% potassium permanganate solution, then wash, filter and dry. Preheat the dried hydroxyapatite to 60°C and keep it warm. S02: 3-5 parts of hydroxyapatite treated with S01, 1-2 parts of stearic acid, 0.02-0.03 parts of manganese powder, 0.02-0.03 parts of chromium powder and 5-8 parts of sodium alginate solution are fully mixed, and then filtered and dried to obtain a hydroxyapatite-based conditioning agent; S03: heat-treating kaolin at 150-160° C. for 10-20 min, then air-cooling to room temperature, and fully blending 3-5 parts of heat-treated kaolin, 1-3 parts of aluminum borate whiskers, 5-8 parts of chitosan solution, and 2-3 parts of sodium dodecylbenzene sulfonate to obtain a kaolin composite whisker solution; S04: ultrasonically treat a hydroxyapatite-based conditioning agent and a kaolin compound whisker solution at a weight ratio of 2:5 to obtain a hydroxyapatite-modified conditioning agent.

[0021] The mass fraction of the sodium alginate solution in this embodiment is 2-5%; the mass fraction of the chitosan solution is 3-5%.

[0022] The ultrasonic power of the ultrasonic treatment in this embodiment is 450-500W, and the ultrasonic time is 20-30min.

[0023] The preparation method of the modified liquid of this embodiment is: S101: irradiating the wollastonite in a proton irradiation box for 10 to 15 minutes at an irradiation power of 350 to 400 W, and obtaining an irradiated wollastonite agent after the irradiation is completed; The irradiated wollastonite agent, lanthanum chloride solution and silane coupling agent KH550 are uniformly mixed in a weight ratio of (3-4):5:1 to obtain a wollastonite active solution; S102: adding yttrium oxide to the regulator in a weight ratio of 2:5, stirring and regulating, and after stirring, filtering and drying to obtain a regulated yttrium oxide body; The adjusted yttrium oxide body and wollastonite active liquid are mixed in a weight ratio of 3:5 and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 hours to obtain a modified liquid.

[0024] Preferably, the stirring temperature of the stirring and adjusting treatment is 55-60° C., the stirring speed is 350-400 r / min, and the stirring time is 1 hour; and the mass fraction of the lanthanum chloride solution is 2-5%.

[0025] The conditioning agent of this embodiment comprises the following raw materials in parts by weight: 2 to 3 parts of nano titanium dioxide, 3 to 5 parts of 5% dopamine hydrochloride solution by mass, 1 to 1.5 parts of urea, 2 to 4 parts of flaky boron nitride and 4 to 6 parts of 4% sodium lignin sulfonate solution by mass.

[0026] The boron nitride flake layer thickness of the present embodiment is 2-3 nm, and the flake diameter is 1-3 µm.

[0027] The cobalt-containing high-tech steel is prepared by the preparation method of the cobalt-containing high-tech steel in this embodiment.

[0028] Example 1 A method for preparing a cobalt-containing high-tech steel in this embodiment comprises the following steps: Step 1: weigh the raw materials according to weight: Fe 55 parts, Mo 2 parts, W 2 parts, V 0.5 parts, Co 0.2 parts, C 0.1 parts, rare earth elements 0.1 parts; Step 2: Smelt the Fe, Mo, W, V, Co and C in step 1 to form a melt, then add the rare earth element and continue smelting for 1-2 hours to obtain a casting liquid; Step 3, injecting the casting liquid into a metal mold preheated to 200° C. for casting to obtain a steel ingot; Step 4, immersing the steel ingot into a sufficient amount of a hydroxyapatite-modified immersion agent for ultrasonic immersion treatment, with an ultrasonic immersion power of 350 W and an ultrasonic time of 20 min. After the immersion is completed, the steel ingot is filtered and dried to obtain an immersion-treated steel ingot; Step 5, performing a solution treatment on the leached steel ingot, and then performing an aging treatment; Step six, coating the surface of the steel ingot processed in step five with the modifying liquid until the surface of the steel ingot is wetted, and then induction heating treatment is performed to obtain the cobalt-containing high-tech steel of the present invention.

[0029] The rare earth elements in this embodiment are neodymium, gadolinium, and scandium mixed in a weight ratio of 2:1:1; The temperature of the solution treatment is 500°C for 1 hour; the temperature of the aging treatment is 350°C for 10 hours; Induction heating treatment adopts distributed induction heating treatment. The specific induction heating method is: First, the sample was induction heated at 790 °C for 2 h, then cooled to 550 °C at a rate of 1 °C / min, induction heated for 1 h, and finally air-cooled to room temperature.

[0030] The preparation method of the hydroxyapatite-modified infusion agent of this embodiment is as follows: S01: First, stir the hydroxyapatite in a sufficient amount of 5% potassium permanganate solution, then wash, filter and dry. Preheat the dried hydroxyapatite to 60°C and keep it warm. S02: 3 parts of hydroxyapatite treated with S01, 1 part of stearic acid, 0.02 parts of manganese powder, 0.02 parts of chromium powder and 5 parts of sodium alginate solution are fully mixed, and then filtered and dried to obtain a hydroxyapatite-based conditioning agent; S03: heat-treating kaolin at 150°C for 10 min, then air-cooling to room temperature, and fully blending 3 parts of heat-treated kaolin, 1 part of aluminum borate whisker, 5 parts of chitosan solution and 2 parts of sodium dodecylbenzene sulfonate to obtain a kaolin polytuning whisker solution; S04: ultrasonically treat a hydroxyapatite-based conditioning agent and a kaolin compound whisker solution at a weight ratio of 2:5 to obtain a hydroxyapatite-modified conditioning agent.

[0031] The mass fraction of the sodium alginate solution is 2%; the mass fraction of the chitosan solution is 3%.

[0032] The ultrasonic power of the ultrasonic treatment in this embodiment is 450W, and the ultrasonic time is 20min.

[0033] The preparation method of the modified liquid of this embodiment is: S101: irradiating the wollastonite in a proton irradiation box for 10 minutes at an irradiation power of 350 W, and obtaining an irradiated wollastonite agent after the irradiation is completed; The irradiated wollastonite agent, lanthanum chloride solution and silane coupling agent KH550 are uniformly mixed in a weight ratio of 3:5:1 to obtain a wollastonite active solution; S102: adding yttrium oxide to the regulator in a weight ratio of 2:5, stirring and regulating, and after stirring, filtering and drying to obtain a regulated yttrium oxide body; The adjusted yttrium oxide body and wollastonite active liquid are mixed in a weight ratio of 3:5 and ball-milled at a ball-milling speed of 1000 r / min for 2 hours to obtain a modified liquid.

[0034] Preferably, the stirring temperature of the stirring and regulating treatment is 55° C., the stirring speed is 350 r / min, and the stirring time is 1 h; and the mass fraction of the lanthanum chloride solution is 2%.

[0035] The conditioning agent of this embodiment comprises the following raw materials in parts by weight: 2 parts of nano titanium dioxide, 3 parts of 5% by mass dopamine hydrochloride solution, 1 part of urea, 2 parts of flake boron nitride and 4 parts of 4% by mass sodium lignin sulfonate solution.

[0036] The boron nitride flake layer thickness of the present embodiment is 2nm, and the flake diameter is 1µm.

[0037] Example 2 A method for preparing a cobalt-containing high-tech steel in this embodiment comprises the following steps: Step 1: weigh the raw materials according to weight: Fe 60 parts, Mo 5 parts, W 4 parts, V 0.8 parts, Co 0.5 parts, C 0.2 parts, rare earth elements 0.2 parts; Step 2: Smelt the Fe, Mo, W, V, Co and C in step 1 to form a melt, then add the rare earth element and continue smelting for 1-2 hours to obtain a casting liquid; Step 3, injecting the casting liquid into a metal mold preheated to 250° C. for casting to obtain a steel ingot; Step 4, immersing the steel ingot into a sufficient amount of a hydroxyapatite-modified immersion agent for ultrasonic immersion treatment, with an ultrasonic immersion power of 400 W and an ultrasonic time of 20 min. After the immersion is completed, the steel ingot is filtered and dried to obtain an immersion-treated steel ingot; Step 5, performing a solution treatment on the leached steel ingot, and then performing an aging treatment; Step six, coating the surface of the steel ingot processed in step five with the modifying liquid until the surface of the steel ingot is wetted, and then induction heating treatment is performed to obtain the cobalt-containing high-tech steel of the present invention.

[0038] The rare earth elements in this embodiment are neodymium, gadolinium, and scandium mixed in a weight ratio of 2:1:1; The temperature of the solution treatment is 540°C for 2 hours; the temperature of the aging treatment is 380°C for 20 hours; Induction heating treatment adopts distributed induction heating treatment. The specific induction heating method is: First, the sample was induction heated at 800 °C for 2 h, then cooled to 560 °C at a rate of 3 °C / min, induction heated for 1 h, and finally air-cooled to room temperature.

[0039] The preparation method of the hydroxyapatite-modified infusion agent of this embodiment is as follows: S01: First, stir the hydroxyapatite in a sufficient amount of 5% potassium permanganate solution, then wash, filter and dry. Preheat the dried hydroxyapatite to 60°C and keep it warm. S02: 5 parts of hydroxyapatite treated with S01, 2 parts of stearic acid, 0.03 parts of manganese powder, 0.03 parts of chromium powder and 8 parts of sodium alginate solution are fully mixed, and then filtered and dried to obtain a hydroxyapatite-based conditioning agent; S03: heat-treating kaolin at 160°C for 20 minutes, then air-cooling to room temperature, and fully blending 5 parts of heat-treated kaolin, 3 parts of aluminum borate whiskers, 8 parts of chitosan solution and 3 parts of sodium dodecylbenzene sulfonate to obtain a kaolin polytuning whisker solution; S04: ultrasonically treat a hydroxyapatite-based conditioning agent and a kaolin compound whisker solution at a weight ratio of 2:5 to obtain a hydroxyapatite-modified conditioning agent.

[0040] The mass fraction of the sodium alginate solution is 5%; the mass fraction of the chitosan solution is 5%.

[0041] The ultrasonic power of the ultrasonic treatment in this embodiment is 500W, and the ultrasonic time is 30min.

[0042] The preparation method of the modified liquid of this embodiment is: S101: irradiating the wollastonite in a proton irradiation box for 15 minutes at an irradiation power of 400 W, and obtaining an irradiated wollastonite agent after the irradiation is completed; The irradiated wollastonite agent, lanthanum chloride solution and silane coupling agent KH550 are uniformly mixed in a weight ratio of 4:5:1 to obtain a wollastonite active solution; S102: adding yttrium oxide to the regulator in a weight ratio of 2:5, stirring and regulating, and after stirring, filtering and drying to obtain a regulated yttrium oxide body; The adjusted yttrium oxide body and wollastonite active liquid are mixed in a weight ratio of 3:5 and ball-milled at a ball-milling speed of 1500 r / min for 2 hours to obtain a modified liquid.

[0043] The stirring temperature of the stirring adjustment treatment is 60° C., the stirring speed is 400 r / min, and the stirring time is 1 h; the mass fraction of the lanthanum chloride solution is 5%.

[0044] The conditioning agent of this embodiment comprises the following raw materials in parts by weight: 3 parts of nano titanium dioxide, 5 parts of 5% by mass dopamine hydrochloride solution, 1.5 parts of urea, 4 parts of flake boron nitride and 6 parts of 4% by mass sodium lignin sulfonate solution.

[0045] The boron nitride flake layer thickness of this embodiment is 3nm; the flake diameter is 3µm.

[0046] Example 3 A method for preparing a cobalt-containing high-tech steel in this embodiment comprises the following steps: Step 1: weigh the raw materials according to weight: Fe 57.5 parts, Mo 3.5 parts, W 3 parts, V 0.65 parts, Co 0.35 parts, C 0.15 parts, rare earth elements 0.15 parts; Step 2: Smelt the Fe, Mo, W, V, Co and C in step 1 to form a melt, then add the rare earth element and continue smelting for 1-2 hours to obtain a casting liquid; Step 3, injecting the casting liquid into a metal mold preheated to 225° C. for casting to obtain a steel ingot; Step 4, immersing the steel ingot into a sufficient amount of a hydroxyapatite-modified immersion agent for ultrasonic immersion treatment, with an ultrasonic immersion power of 375 W and an ultrasonic time of 20 min. After the immersion is completed, the steel ingot is filtered and dried to obtain an immersion-treated steel ingot; Step 5, performing a solution treatment on the leached steel ingot, and then performing an aging treatment; Step six, coating the surface of the steel ingot processed in step five with the modifying liquid until the surface of the steel ingot is wetted, and then induction heating treatment is performed to obtain the cobalt-containing high-tech steel of the present invention.

[0047] The rare earth elements in this embodiment are neodymium, gadolinium, and scandium mixed in a weight ratio of 2:1:1; The temperature of the solution treatment is 520°C for 1.5 hours; the temperature of the aging treatment is 365°C for 15 hours; Induction heating treatment adopts distributed induction heating treatment. The specific induction heating method is: First, the sample was induction heated at 795 °C for 2 h, then cooled to 55 °C at a rate of 2 °C / min, induction heated for 1 h, and finally air-cooled to room temperature.

[0048] The preparation method of the hydroxyapatite-modified infusion agent of this embodiment is as follows: S01: First, stir the hydroxyapatite in a sufficient amount of 5% potassium permanganate solution, then wash, filter and dry. Preheat the dried hydroxyapatite to 60°C and keep it warm. S02: 4 parts of hydroxyapatite treated with S01, 1.5 parts of stearic acid, 0.025 parts of manganese powder, 0.025 parts of chromium powder and 6.5 parts of sodium alginate solution are fully mixed, and then filtered and dried to obtain a hydroxyapatite-based conditioning agent; S03: heat-treating kaolin at 155°C for 15 minutes, and then air-cooling to room temperature, and fully blending 4 parts of heat-treated kaolin, 2 parts of aluminum borate whiskers, 6.5 parts of chitosan solution and 2.5 parts of sodium dodecylbenzene sulfonate to obtain a kaolin polytuning whisker solution; S04: ultrasonically treat a hydroxyapatite-based conditioning agent and a kaolin compound whisker solution at a weight ratio of 2:5 to obtain a hydroxyapatite-modified conditioning agent.

[0049] The mass fraction of the sodium alginate solution is 3.5%; the mass fraction of the chitosan solution is 4%.

[0050] The ultrasonic power of the ultrasonic treatment in this embodiment is 470W, and the ultrasonic time is 25min.

[0051] The preparation method of the modified liquid of this embodiment is: S101: irradiating the wollastonite in a proton irradiation box for 12.5 minutes at an irradiation power of 375 W, and obtaining an irradiated wollastonite agent after the irradiation is completed; The irradiated wollastonite agent, lanthanum chloride solution and silane coupling agent KH550 are uniformly mixed in a weight ratio of 3.5:5:1 to obtain a wollastonite active solution; S102: adding yttrium oxide to the regulator in a weight ratio of 2:5, stirring and regulating, and after stirring, filtering and drying to obtain a regulated yttrium oxide body; The adjusted yttrium oxide body and wollastonite active liquid are mixed in a weight ratio of 3:5 and ball-milled at a ball-milling speed of 1250 r / min for 2 h to obtain a modified liquid.

[0052] Preferably, the stirring temperature of the stirring and adjusting treatment is 57.5° C., the stirring speed is 375 r / min, and the stirring time is 1 h; and the mass fraction of the lanthanum chloride solution is 3.5%.

[0053] The conditioning agent of this embodiment comprises the following raw materials in parts by weight: 2.5 parts of nano titanium dioxide, 4 parts of 5% by mass dopamine hydrochloride solution, 1.25 parts of urea, 3 parts of flaky boron nitride and 5 parts of 4% by mass sodium lignin sulfonate solution.

[0054] The boron nitride flake layer thickness of the present embodiment is 2.5 nm, and the flake diameter is 2 µm.

[0055] Comparative Example 1 The difference from Example 3 is that no rare earth element is added.

[0056] Comparative Example 2 The difference from Example 3 is that no hydroxyapatite-modified infusion agent was used.

[0057] Comparative Example 3 The difference from Example 3 is that no hydroxyapatite-based conditioning agent is added in the preparation of the hydroxyapatite-modified infusion conditioning agent.

[0058] Comparative Example 4 The difference from Example 3 is that the hydroxyapatite-based conditioning agent does not contain hydroxyapatite treated with S01.

[0059] Comparative Example 5 The difference from Example 3 is that no manganese powder or chromium powder is added to the hydroxyapatite-based regulator.

[0060] Comparative Example 6 The difference from Example 3 is that no kaolin whisker solution is added in the preparation of the hydroxyapatite-modified infusion agent.

[0061] Comparative Example 7 The difference from Example 3 is that no heat-treated kaolin is added to the kaolin composite whisker solution.

[0062] Comparative Example 8 The difference from Example 3 is that no aluminum borate whiskers are added to the kaolin composite whisker solution.

[0063] Comparative Example 9 The difference from Example 3 is that no modification liquid treatment was used.

[0064] Comparative Example 10 The difference from Example 3 is that no regulated yttrium oxide is added to the modified solution.

[0065] Comparative Example 11 The difference from Example 3 is that no regulator is added to the regulated yttrium oxide body.

[0066] Comparative Example 12 The difference from Example 3 is that no wollastonite active liquid is added to the adjusted yttrium oxide body. The specific process is: yttrium oxide is added to the regulator in a weight ratio of 2:5 and stirred for adjustment. After the stirring is completed, the adjusted yttrium oxide body is obtained, and other process conditions and raw materials remain unchanged.

[0067] The products of Examples 1-3 and Comparative Examples 1-12 were tested for wear resistance, impact resistance and hardness under normal conditions, as well as corrosion resistance and heat and cold stability. The products were placed in 2% hydrochloric acid mist for 12 hours, then placed at 70°C for 12 hours, and then transferred to -5°C for 12 hours. The above is one cycle. The cycle was repeated 10 times to test the corrosion resistance and heat and cold stability of the products. The test results are as follows:

[0068] It is concluded from Examples 1-3 and Comparative Examples 1-12 that The product of Example 3 of the present invention can achieve coordinated improvement in wear resistance, impact resistance and hardness under normal conditions, and at the same time, the product has significant effects on corrosion resistance, cold and heat stability; The present invention does not use the leaching agent based on hydroxyapatite modification and the modifying liquid treatment, and the performance of the product deteriorates significantly. The two are used in combination and the synergy is achieved, and the product performance effect is most obvious. In the preparation of the hydroxyapatite-modified leaching agent, no hydroxyapatite-based regulator was added to the hydroxyapatite-based regulator, no manganese powder or chromium powder was added to the hydroxyapatite-based regulator, no kaolin compound whisker liquid was added to the preparation of the hydroxyapatite-modified leaching agent, no heat-treated kaolin was added to the kaolin compound whisker liquid, and no aluminum borate whisker was added to the kaolin compound whisker liquid. The performance of the products all showed a trend of deterioration to varying degrees. At the same time, the performance stability of the product deteriorated significantly without the addition of kaolin compound whisker liquid. The performance coordination effect of the product was poor without the addition of hydroxyapatite treated with S01. The performance effect of the hydroxyapatite-modified leaching agent prepared by the hydroxyapatite-based regulator obtained by the specific method of the present invention and the kaolin compound whisker liquid was the most significant, and the effects of other methods were not as obvious as those of the present invention. When no adjusted yttrium oxide body is added to the modified liquid, no regulator is added to the adjusted yttrium oxide body, and no wollastonite active liquid is added to the adjusted yttrium oxide body, the performance of the products tends to deteriorate. The modified liquid obtained by the specific method of the present invention has the most significant product performance effect. At the same time, when no regulator is added to the adjusted yttrium oxide body, the performance of the product deteriorates more significantly.

[0069] Since the regulator has a significant impact on the performance of the product, further research is needed: The conditioning agent comprises the following raw materials in parts by weight: 2.5 parts of nano titanium dioxide, 4 parts of 5% by mass dopamine hydrochloride solution, 1.25 parts of urea, 3 parts of flaky boron nitride and 5 parts of 4% by mass sodium lignin sulfonate solution.

[0070] The boron nitride flake layer thickness of the present embodiment is 2.5 nm, and the flake diameter is 2 µm.

[0071] Experimental Example 1 The only difference from Example 3 is that no nano titanium dioxide is added to the regulator.

[0072] Experimental Example 2 The only difference from Example 3 is that no flake boron nitride is added to the regulator.

[0073] Experimental Example 3 The only difference from Example 3 is that no urea is added to the regulator.

[0074] Experimental Example 4 The only difference from Example 3 is that no sodium lignin sulfonate solution is added to the regulator.

[0075] Experimental Example 5 The only difference from Example 3 is that no dopamine hydrochloride solution is added to the regulator.

[0076]

[0077] It can be seen from Experimental Examples 1-5 that no flake boron nitride is added to the regulator, and the product performance change trend has the greatest influence among the factors of the regulator, followed by no nano titanium dioxide being added to the regulator. At the same time, no urea is added to the regulator, no sodium lignin sulfonate solution is added to the regulator, and no dopamine hydrochloride solution is added to the regulator. The performance of the product has a tendency to deteriorate. Only by using the raw material combination of the present invention, the performance effect of the product is the most significant. The performance effect of the product is the most significant when flake boron nitride is combined with nano titanium dioxide and then adjusted with the specific raw material ratio of the present invention. The use of other methods instead is not as obvious as the effect of the present invention.

[0078] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0079] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing cobalt-containing high-tech steel, characterized in that: The following steps are involved: Step 1: weigh the raw materials according to weight: Fe 55-60 parts, Mo 2-5 parts, W 2-4 parts, V 0.5-0.8 parts, Co 0.2-0.5 parts, C 0.1-0.2 parts, rare earth elements 0.1-0.2 parts; Step 2: Smelt the Fe, Mo, W, V, Co and C in step 1 to form a melt, then add the rare earth element and continue smelting for 1-2 hours to obtain a casting liquid; Step 3, injecting the casting liquid into a metal mold preheated to 200-250° C. for casting to obtain a steel ingot; Step 4, immersing the steel ingot into a sufficient amount of a hydroxyapatite-modified immersion agent for ultrasonic immersion treatment, the ultrasonic immersion power is 350-400W, the ultrasonic time is 20min, and after the immersion is completed, the immersion is filtered and dried to obtain the immersion-treated steel ingot; Step 5, performing a solution treatment on the leached steel ingot, and then performing an aging treatment; Step six, coating the surface of the steel ingot processed in step five with the modifying liquid until the surface of the steel ingot is soaked, and then induction heating treatment is performed to obtain cobalt-containing high-tech steel.

2. The method for preparing a cobalt-containing high-tech steel according to claim 1, characterized in that: The rare earth elements are neodymium, gadolinium and scandium mixed in a weight ratio of 2:1:1; The temperature of the solution treatment is 500-540°C for 1-2 hours; the temperature of the aging treatment is 350-380°C for 10-20 hours; Induction heating treatment adopts distributed induction heating treatment. The specific induction heating method is: First, induction heating was performed at 790-800°C for 2 h, then the temperature was lowered to 550-560°C at a rate of 1-3°C / min, induction heating was performed for 1 h, and finally air-cooled to room temperature.

3. The method for preparing a cobalt-containing high-tech steel according to claim 1, characterized in that: The preparation method of the hydroxyapatite-modified infusion agent is as follows: S01: First, stir the hydroxyapatite in a sufficient amount of 5% potassium permanganate solution, then wash, filter and dry. Preheat the dried hydroxyapatite to 60°C and keep it warm. S02: 3-5 parts of hydroxyapatite treated with S01, 1-2 parts of stearic acid, 0.02-0.03 parts of manganese powder, 0.02-0.03 parts of chromium powder and 5-8 parts of sodium alginate solution are fully mixed, and then filtered and dried to obtain a hydroxyapatite-based conditioning agent; S03: heat-treating kaolin at 150-160° C. for 10-20 min, then air-cooling to room temperature, and fully blending 3-5 parts of heat-treated kaolin, 1-3 parts of aluminum borate whiskers, 5-8 parts of chitosan solution, and 2-3 parts of sodium dodecylbenzene sulfonate to obtain a kaolin composite whisker solution; S04: ultrasonically treat a hydroxyapatite-based conditioning agent and a kaolin compound whisker solution at a weight ratio of 2:5 to obtain a hydroxyapatite-modified conditioning agent.

4. The method for preparing a cobalt-containing high-tech steel according to claim 3, characterized in that: The mass fraction of the sodium alginate solution is 2-5%; the mass fraction of the chitosan solution is 3-5%.

5. The method for preparing a cobalt-containing high-tech steel according to claim 3, characterized in that: The ultrasonic power of the ultrasonic treatment is 450-500W, and the ultrasonic time is 20-30min.

6. The method for preparing a cobalt-containing high-tech steel according to claim 1, characterized in that: The preparation method of the modified liquid is: S101: irradiating the wollastonite in a proton irradiation box for 10 to 15 minutes at an irradiation power of 350 to 400 W, and obtaining an irradiated wollastonite agent after the irradiation is completed; The irradiated wollastonite agent, lanthanum chloride solution and silane coupling agent KH550 are uniformly mixed in a weight ratio of (3-4):5:1 to obtain a wollastonite active solution; S102: adding yttrium oxide to the regulator in a weight ratio of 2:5, stirring and regulating, and after stirring, filtering and drying to obtain a regulated yttrium oxide body; The adjusted yttrium oxide body and wollastonite active liquid are mixed in a weight ratio of 3:5 and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 hours to obtain a modified liquid.

7. The method for preparing a cobalt-containing high-tech steel according to claim 6, characterized in that: The stirring temperature of the stirring adjustment treatment is 55-60° C., the stirring speed is 350-400 r / min, and the stirring time is 1 hour; the mass fraction of the lanthanum chloride solution is 2-5%.

8. The method for preparing cobalt-containing high-tech steel according to claim 6, characterized in that: The regulator comprises the following raw materials in parts by weight: 2 to 3 parts of nano titanium dioxide, 3 to 5 parts of 5% dopamine hydrochloride solution by mass, 1 to 1.5 parts of urea, 2 to 4 parts of flaky boron nitride and 4 to 6 parts of 4% sodium lignin sulfonate solution by mass.

9. The method for preparing cobalt-containing high-tech steel according to claim 8, characterized in that: The flake-shaped boron nitride has a layer thickness of 2 to 3 nm and a flake diameter of 1 to 3 μm.

10. Cobalt-containing high-grade steel prepared by the method for preparing cobalt-containing high-grade steel according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Hardened martensitic steel having low cobalt content, process for manufacturing part from this steel, and parts thus obtained

    CN102131947A

  • High-chromium cobalt-containing tungsten-containing martensite heat-resistant cast steel material and preparation method thereof

    CN118497612A

  • Modified hard alloy cutter and preparation method

    CN118951022A

  • NANO-precipitation strengthened ultra-high strength corrosion resistant structural steels

    WO2004108970A2

  • Hardened martensitic steel having a low cobalt content, process for manufacturing a part from this steel, and part thus obtained

    WO2010007297A1

Cited By

  • High-ductility low-density steel and preparation method thereof

    CN121737584A

  • A high ductility low density steel and a method of making the same

    CN121737584B